2012
DOI: 10.1530/eje-11-0945
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol as a diagnostic tool for Cushing's syndrome and adrenal insufficiency: improved screening by an automatic immunoassay

Abstract: Background: Salivary cortisol is increasingly used to assess patients with suspected hypo-and hypercortisolism. This study established disease-specific reference ranges for an automated electrochemiluminescence immunoassay (ECLIA). Methods: Unstimulated saliva from 62 patients with hypothalamic-pituitary disease was collected at 0800 h. A peak serum cortisol level below 500 nmol/l during the insulin tolerance test (ITT) was used to identify hypocortisolism. Receiver-operating characteristic (ROC) analysis allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 26 publications
7
55
1
2
Order By: Relevance
“…As reported in some studies (2,5,6,7,10,11,12,14), we found that LNSC levels were higher in CS; a threshold value above 5.24 ng/ml provided a good accuracy to detect endogenous hypercortisolism, and in particular to discover CD, the most common form. LNSC was able to differentiate CS patients from the control population, which included not only healthy subjects but also patients with suspected CS, and our proposed threshold value is consistent with other data reported in the literature and obtained with RIAs (5, 11, 23).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…As reported in some studies (2,5,6,7,10,11,12,14), we found that LNSC levels were higher in CS; a threshold value above 5.24 ng/ml provided a good accuracy to detect endogenous hypercortisolism, and in particular to discover CD, the most common form. LNSC was able to differentiate CS patients from the control population, which included not only healthy subjects but also patients with suspected CS, and our proposed threshold value is consistent with other data reported in the literature and obtained with RIAs (5, 11, 23).…”
Section: Discussionsupporting
confidence: 78%
“…Salivary cortisol is increasingly being used to assess hyper-or hypocortisolism (1,2). The measurement of late-night salivary cortisol (LNSC) levels in combination with the 1 mg dexamethasone suppression test (DST) and that of urinary free cortisol (UFC) levels have been proposed as the first-line laboratory tests in the diagnosis of Cushing's syndrome (CS) (3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salivary steroids are a non-invasive, easily repeated, stress-free way to measure circulating free hormone levels (12,13), recently recommended for assessing cortisol profiles in healthy people (14,15) and in patients with hypothalamic-pituitary-adrenal (HPA) axis disorders (16,17).…”
Section: Introductionmentioning
confidence: 99%